The centrality of Christ in the theology of Thomas F. Torrance: some dogmatic implications - Molnar, Paul D. (T&T Clark, 2024)
"One of the leading systematic theologians Paul D. Molnar examines the theology of Thomas F. Torrance, explores his view of justification by grace alone, emphasizing its relation to Liberation Theology. Molnar discusses Rahner's presuppositions and conclusions on the subject. As well as explores the current issues surrounding the Chalcedon"--